2001
DOI: 10.1051/vetres:2001141
|View full text |Cite
|
Sign up to set email alerts
|

Myocastor coypus as a reservoir host of Fasciola hepatica in France

Abstract: -To clarify the role of the nutria Myocastor coypus in the epidemiology of domestic fasciolosis in Loire-Atlantique (department of western France), 438 nutrias were trapped in 9 humid areas of the department and 304 nutrias were trapped in 3 farms where Fasciola hepatica was present; all animals were necropsied. Liver flukes were found in 160 nutrias: 38 nutrias randomly taken in the department (8.7%) and 122 trapped in fasciolosis areas (40.1%). The average parasitic burden was 5.7 flukes per nutria. Sixty-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…A similar lack of total effectiveness has been reported in previous studies (Torgerson and Claxton 1999). In the present study, the residual presence of this parasite was probably due to contamination of the pasture by infected hares, which may act as competent reservoirs, as found for the nutria (Myocastor cypus) by Ménard et al (2001) in France and for the black rat (Rattus rattus) by Adela Valero et al (2002) in Corsica.…”
Section: Discussionsupporting
confidence: 53%
“…A similar lack of total effectiveness has been reported in previous studies (Torgerson and Claxton 1999). In the present study, the residual presence of this parasite was probably due to contamination of the pasture by infected hares, which may act as competent reservoirs, as found for the nutria (Myocastor cypus) by Ménard et al (2001) in France and for the black rat (Rattus rattus) by Adela Valero et al (2002) in Corsica.…”
Section: Discussionsupporting
confidence: 53%
“…Fascioliasis was known to occur in nutria from a number of countries including both American and European countries to which this rodent has been introduced (Pridham, 1966;Pascal et al, 2003;Pelloté et al, 2008). In fact, because of its eco-ethologic characteristic, the nutria could be a potential wild reservoir of F. hepatica in Brazil (Santos, 1992) and in France (Menard et al, 2001) where a prevalence of 36%, the triple of our figures, was reported. Examinations of faecal samples have also revealed the presence of Sporozoa, being coccidia (Eimeria myopotami and E. nutriae) the most prevalent.…”
Section: Discussionmentioning
confidence: 58%
“…For example, S. myopotami is a zoonotic parasite that causes a severe itchy cutaneous rash some hours after contact with water or soil contaminated by its larvae (Bonilla et al 2000). In contrast with previous studies in Europe, hepatic flukes were not found in the coypus (Menard et al 2001). The antibody prevalence (30%) of the cosmopolitan zoonotic protozoan T. gondii confirmed the wide presence of this parasite in coypus.…”
mentioning
confidence: 72%